OpenStack : building a cloud environment : learn how you can put the features of OpenStack to work in the real world in this comprehensive path : a course in three modules.: building a cloud environment : learn how you can put the features of OpenStack to work in the real world in this comprehensive path : a course in three modules. (2016) - Shrivastwa, Alok
No abstract available